ASSOCIATION OF METABOLIC SYNDROME WITH CARPAL TUNNEL SYNDROME - Dr Maha Ali; Dr Bashir A. Soomro; Dr Filza Qureshi; Dr Hudaibiya Ayub; Dr Rida Younis; Dr Hira Fatima (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background:Carpal tunnel syndrome (CTS) is an issue that commonly occurs when the median nerve is narrowed at the wrist. Studies are conducted on the association of metabolic syndrome with CTS, but link between them is not well understood among South Asians.Objective: To investigate the association between Metabolic Syndrome and Carpal Tunnel Syndrome.Methodology: This case-control study took place at Ziauddin University's Neurology Department in Karachi for the time duration of six months, i-e, 1st June, 2024 to 30th November, 2024. There were 152 metabolic syndrome patients, 76 of whom had CTS (referred to as cases) and 76 of whom did not (referred to as controls). SPSS 25 was used to analyze the data, and the Mann-Whitney U, t-test, and chi-square tests were used to compare the groups. Statistical significance was defined as a p-value of less than 0.05.Results: Higher CTS severity levels were substantially correlated with metabolic syndrome (p=0.0001). In addition to having lower HDL cholesterol and higher fasting triglyceride levels, patients with metabolic syndrome also had greater prevalences of symptoms such as pain, numbness, and weakness (p=0.0001). Additionally, the group with metabolic syndrome had significantly higher diastolic blood pressure (p=0.007). The proportion of age and gender was similar between groups.Conclusion: Metabolic syndrome is strongly associated with both the presence and increased clinical severity of CTS. Screening for metabolic syndrome in CTS patients may facilitate early interventions to improve clinical outcomes.